Investigating the Effect of Relative Firms Profitability on Stock Return Sensitivity to Industry-Level News (مجله دانش حسابداری, 2014)
Relative firm profitability within industry as a measure of competitiveness reflects the business strengths and weaknesses of the firm, and affects the reaction of stock returns to industry-level news. Relative profitability is affected by operational decisions of the firm that is associated with the decisions of other firms in the industry. So, such an operational dependency between competing firms may affect the firm's cash flows and change behavior of stock return. Hence, stock return of the firms with operational strengths, compared with weak firms, is less sensitive to industry-level news. In order to examine the effects of relative firm's profitability as a measure of competitiveness within industry on stock return behavior, data of 130 firms in the period of 1381 to 1390 were analyzed. Regression models were estimated, using the panel data model. Industry returns are used as proxy for industry-level news. Findings indicate that there is a negative relationship between relative firm’s profitability and stock return sensitivity to industry-level news. Also, relative profitability explains return sensitivity well, when there is positive industry news; and there is a negative relationship between relative cost efficiency and stock return sensitivity to industry-level news.